Procedimentos de avaliação em terapia de casais a partir de múltiplos instrumentos - Marturano, Edna Maria; Bolsoni-Silva, Alessandra Turini [UNESP] (My University, 2010)
Conjugal problems may damage parents and children relationships favoring the appearance of behavior problems, as well as causing psychological problems. Given the lack of studies which value several interrelated behavioral repertoires, the present paper aims at presenting assessment results employing multiple instruments in regards to the three couples that sought clinical services at a University clinic. Results indicated that participants were presenting communication deficits, problem solving difficulties, and problems in expressing affection confirming literature findings. Problems in other areas were also reported, which influenced the marital relationship. It stands out that the children were presenting indications of behavior problems. The relevance of data collection applying different instruments is discussed, and it is necessary that intervention programs consider individual difficulties, besides setting up singular objectives for each person searching for service.

Os problemas conjugais podem prejudicar o relacionamento entre pais e filhos, favorecendo o surgimento de problemas de comportamento e, também, podem suscitar problemas psicológicos. Diante da carência de estudos que avaliem diversos repertórios comportamentais que se inter-relacionam, o presente trabalho tem por objetivo apresentar resultados de avaliações, a partir de múltiplos instrumentos, de três casais que buscaram atendimento em uma clínica escola. Os resultados indicaram que os participantes apresentavam déficits em comunicação, em resolução de problemas e em expressão de afeto, confirmando achados da literatura. Foram relatados também problemas em outras áreas, os quais influenciavam no relacionamento conjugal. Destaca-se que os filhos apresentavam indicativos de problemas de comportamento. Discute-se a relevância de colher dados a partir de diferentes instrumentos e a necessidade de programas de intervenção considerarem as dificuldades individuais, além de estabelecerem objetivos próprios para cada pessoa que busca por atendimento.
Assessment procedure in marital therapy using multiple instruments
Keywords: Couple therapy; Social skills; Behavior problems; Assessment; Terapia de casais; Habilidades sociais; Problemas de comportamento; Avaliação